Teripang Pasir Meningkatkan Kandungan Antioksidan Superoksida Dismutase pada Pankreas Tikus Diabetes (SEA CUCUMBER INCREASED ANTIOXIDANT SUPEROXIDE DISMUTASE IN THE PANCREATIC TISSUE OF DIABETIC RATS) - Wresdiyati, Tutik; Karmila, Ani; Astawan, Made; Karnila, Rahman (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
High level of blood glucose is an indicator for diabetes mellitus (DM) condition. The condition iscaused by low level of insulin secretion or impairement of insulin receptor. The number of DM patientincreases every year. The World Health Organization reported that the number of DM patient in Indonesiawas the 4th highest in the world, after following China, India, and the United States of America, respectively.This study was conducted to analyze the effect of sea cucumber (Holothuria scabra J) on the profile ofantioxidant copper, zinc-superoxide dismutase (Cu, Zn-SOD) in the pancreatic tissues of diabetic rats. Atotal of 25 male white rats (Sprague Dawley) were used in this study. They were divided into five groups;(1) negative control (KN), (2) positive control, diabetic rats (KP), (3) diabetic rats treated with hydrolyzatedprotein of sea cucumber (HDL), (4) diabetic rats treated with concentrated protein of sea cucumber (KST),and (5) diabetic rats treated with isolated protein of sea cucumber (ISL), respectively. Diabetic conditionwas obtained by alloxan injection 110 mg/kg bw. The treatments were done for 28 days. At the end oftreatment period, the rats were sacrificed and pancreatic tissues were collected and fixed in Bouin solution and then processed to paraffin embedding standard method. The tissues were then stained withimmunohistochemical staining techniques using monoclonal antibody of Cu, Zn-SOD. The results showedthat treatment of HDL, KST, and ISL of sea cucumber (Holothuria scabra J) increased the content ofantioxidant Cu, Zn-SOD either in Langerhans islets and acinar cells of pancreatic tissues-diabetic rats.The HDL of sea cucumber treatment gave the best effect in increasing the antioxidant content of Cu, Zn-SOD in pancreatic tissue of diabetic rats.
Keywords: antioxidant Cu,Zn-SOD, diabetes mellitus, immunohistochemistry, pancreas,sea cucumber (Holothuria scabra J)